Investment decisions under uncertainty - Sunanda Sen (Levy Economics Institute of Bard College, 2018)
Divergent trends, as observed, between growth in the financial and real sectors of the global economy entail the need for further research, especially on the motivations behind investment decisions. Investments in market economies are generally guided by call-put option pricing models - which rely on an ergodic notion of probability that conforms to a normal distribution function. This paper considers critiques of the above models, which include Keynes's Treatise on Probability (1921) and the General Theory (1936), as well as follow-ups in the post-Keynesian approaches and others dealing with "fundamental uncertainty." The methodological issues, as can be pointed out, are relevant in the context of policy issues and social institutions, including those subscribed to by the ruling state. As it has been held in variants of institutional economics subscribed to by John Commons, Thorstein Veblen, Geoffrey Hodgeson, and John Kenneth Galbraith, social institutions remain important in their capacity as agencies that influence individual behavior with their "informational-cognitive" functions in society. By shaping business concerns and strategies, social institutions have a major impact on investment decisions in a capitalist system. The role of such institutions in investment decisions via policy making is generally neglected in strategies based on mainstream economics, which continue to rely on optimization of stock market returns based on imprecise estimations of probability.
Keywords: B25; E02; E12; E22; G01; G11; 330; Uncertainty; Probability; Weights; Investment; Keynes; Institutional Economics